Optimal Data Scheduling in Hybrid CDN-P2P Video on Demand System - Sudhir N. Dhage, Deepali Tatyarao Biradar (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The proliferation of various video applications like video telephony, video conferencing and VoD (Video on Demand) has led to a heterogeneous user base on the Internet. VoD systems empower users with efficient control over video access, enabling them to stream content at their convenience. A Hybrid Peer-to-peer CDN based video on demand systems is an attractive solution for VoD service providers. It combines a traditional CDN with a P2P overlay for exchanging video chunks, reducing the cost of the CDN. However, P2P overlay in VoD systems face challenges, including issues like increase in start-up delay for playing video, underutilization of peer resources, and excessive server load, significantly impacting viewers’ quality-of-service (QoS). Efficient data scheduling emerges as a pivotal concern among these challenges, focusing on the effective transmission and dispatching of data segments within the system. This paper introduces a data scheduling approach using swarm intelligence optimization algorithm -Crow Search Algorithm (CSA). The proposed approach first establishes priorities for chunk requests to ensure prompt handling of high-priority requests. By leveraging the CSA, the optimal peer among the neighbour which caches the requested chunks is selected as the parent for the chunk. The effectiveness of the proposed approach is assessed through simulations, revealing superior performance compared to existing methods and resulting in enhanced system efficiency